A new adaptive time step method for unsteady flow simulations in a human lung. Issue 8 (11th June 2017) - Fenández-Tena, Ana; Marcos, Alfonso C.; Martínez, Cristina; Keith Walters, D.
Abstract: The innovation presented is a method for adaptive time-stepping that allows clustering of time steps in portions of the cycle for which flow variables are rapidly changing, based on the concept of using a uniform step in a relevant dependent variable rather than a uniform step in the independent variable time. A user-defined function was developed to adapt the magnitude of the time step (adaptive time step) to a defined rate of change in inlet velocity. Quantitative comparison indicates that the new adaptive time stepping method significantly improves accuracy for simulations using an equivalent number of time steps per cycle.